Calcium stabilizes the strongest protein fold. Issue 1 (December 2018) - Milles, Lukas; Unterauer, Eduard; Nicolaus, Thomas; Gaub, Hermann
Abstract Staphylococcal pathogens adhere to their human targets with exceptional resilience to mechanical stress, some propagating force to the bacterium via small, Ig-like folds called B domains. We examine the mechanical stability of these folds using atomic force microscopy-based single-molecule force spectroscopy. The force required to unfold a single B domain is larger than 2 nN – the highest mechanostability of a protein to date by a large margin. B domains coordinate three calcium ions, which we identify as crucial for their extreme mechanical strength. When calcium is removed through chelation, unfolding forces drop by a factor of four. Through systematic mutations in the calcium coordination sites we can tune the unfolding forces from over 2 nN to 0.15 nN, and dissect the contribution of each ion to B domain mechanostability. Their extraordinary strength, rapid refolding and calcium-tunable force response make B domains interesting protein design targets. Staphylococcal pathogens adhere to their human targets using adhesins, which can withstand extremely high forces. Here, authors use single-molecule force spectroscopy to determine the similarly high unfolding forces of B domains that link the adhesin to the bacterium.